ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA OPERASI HITUNG PECAHAN SISWA KELAS V-A UPTD SDN 014685 SIUMBUT BARU - Anim Anim; Fildzah Rizkiah Damanik; Amanda Chantika Sari Br Purba; Yovi Dwi Ramadhani (Smart Education, 2025)
Abstract: This study aims to analyze the mathematical problem-solving ability of fifth-grade students at uptd sdn 014685 siumbut baru in solving fraction operation problems. The research subjects consisted of 16 students who were present during the activity. The instrument used consisted of three story-problem items that included various fraction operations (addition, subtraction, multiplication, and division). The results showed that most students experienced difficulties in determining the appropriate operation to use and in simplifying fractions. students also faced challenges in identifying important information in the story problems. Based on the analysis using polya’s problem-solving steps, the main difficulties occurred in the stages of understanding the problem and planning the solution. These findings indicate that students’ abilities in solving fraction operations are still categorized as low. this study recommends the use of visual media and contextual exercises to improve students’ understanding of fraction operation concepts. Keywords: Problem-Solving Ability, Fraction Operations, Elementary School Students Abstrak: Penelitian ini bertujuan untuk menganalisis kemampuan pemecahan masalah matematika siswa kelas V-A UPTD SDN 014685 Siumbut Baru dalam menyelesaikan soal operasi hitung pecahan. Subjek penelitian terdiri atas 16 siswa yang hadir pada saat pelaksanaan kegiatan. Instrumen yang digunakan berupa tiga soal cerita yang mencakup operasi pecahan (penjumlahan, pengurangan, perkalian, dan pembagian). Hasil penelitian menunjukkan bahwa mayoritas siswa mengalami kesulitan dalam menentukan operasi hitung yang tepat untuk menyderhanakan pecahan. Siswa juga mengalami hambatan dalam mengidentifikasi informasi penting pada soal cerita. Berdasarkan analisis menggunakan langkah pemecahan masalah menurut (Polya), kesulitan utama terjadi pada tahap memahami masalah dan merencanakan penyelesaian. Hasil tersebut menunjukkan bahwa kemampuan siswa dalam melakukan operasi hitung pecahan masih tergolong rendah. Penelitian ini merekomendasikan penggunaan media visual serta latihan kontekstual untuk meningkatkan pemahaman siswa terhadap konsep operasi pecahan. Kata Kunci: Kemampuan Pemecahan Masalah, Operasi Hitung Pecahan, Siswa Sekolah Dasar